Variation of diagnostic criteria in women with chronic endometritis and its effect on reproductive outcomes: A systematic review and meta-analysis. (August 2020) - Huang, Weiyu; Liu, Bo; He, Yonghua; Xie, Yiran; Liang, Ting; Bi, Yin; Yuan, Lifang; Qin, Aiping; Wang, Yao; Yang, Yihua
Highlights: Chronic endometritis may leads to reproductive failure. Current diagnostic criteria of chronic endometritis are inconsistent. Inconsistent criteria impact the therapeutic protocol and reproductive outcomes. Consistent criteria need to be established. Abstract: This meta-analysis aimed to evaluate the variation in the diagnostic criteria for chronic endometritis (CE) and its effect on reproductive outcomes. A search of the academic literature was conducted in various databases including PubMed, Embase, Cochrane Library, and Chinese National Knowledge Internet. Studies published in English or Chinese prior to October 1, 2019, were included in the primary screen. Data on the CE incidence rate, cure rate after antibiotic therapy, clinical pregnancy rate, miscarriage rate, and live birth rate were extracted and analyzed. Twelve eligible studies involving 1879 patients were included in this meta-analysis. Compared with strict diagnostic criteria, studies that used broad diagnostic criteria to identify CE reported a higher incidence rate (odds radio [ OR ] = 2.96, 95% confidence interval [CI]: 1.13–6.44), clinical pregnancy rate ( OR = 1.83, 95 % CI: 1.18–2.8), and live birth rate ( OR = 2.08, 95 % CI: 1.43–3.02). Compared with a short treatment course, a longer course of antibiotic treatment significantly improved the cure rate of CE ( OR = 0.29, 95% CI: 0.18−0.47). Based on these findings, variation in the diagnostic criteria may alter the incidence rate, clinical pregnancy rate, and live birth rate of women with CE. A consensus on the diagnostic criteria must be established to obtain a better understanding of and additional information about CE.